Long time no see - Isaacs, Susan, 1943- (New York HarperCollins Publishers, 2001)
Recently widowed, Judith Singer cannot get her former lover, Nelson Sharpe of the Nassau County Police Department, out of her mind, as she investigates the disappearance of Courtney Logan, the wife of a man with ties to the Long Island mob.
Keywords: Women detectives -- New York (State) -- Long Island -- Fiction; Organized crime -- Fiction; Missing persons -- Fiction; Widows -- Fiction; Nassau County (N.Y.) -- Fiction; Long Island (N.Y.) -- Fiction